The Effect Of Role Play Strategy In Teaching Vocabulary At The Eighth Grade Of SMP Negeri 5 Pematang Siantar - Eka Ria Oktavia Ginting Munthe; Yanti kristina Sinaga; Christian Neni Purba (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The aim of this research is to look at The Effect Of Role Play Strategy In Teaching Vocabulary At The Eighth Grade Of Smp Negeri 5 Pematang Siantar. This research would employ a quasi-experimental design with a quantitative research and a "pre-test and post-test" methodology. The objective of the research was to determine whether or not eighth grade children learn vocabulary well through role-playing. The researcher used just two classes as samples. The experimental group is VIII-3, whereas the control group is VIII-4. The mean achievement of these two groups is comparable. Where each class has 31 students. The VIII-3 class was designated as the experimental group, and they would teach through Role Play Strategy, while the VIII-4 class was designated as the control group, and they would not be employing any Role Play Strategy. From the results of the data analysis in the previous study, it can be concluded that Role Play Strategy plays a key role in helping students improve their vocabulary. The use of the Role Play Strategy can help students become more proficient in vocabulary. During the vocabulary lesson in the classroom, the students are more engaged and exhibit greater creativity and innovation. T-test > T-table (3.9 > 1.671), based on the analysis results at the 5% significance level. It also shows that (Ho) was rejected but (Ha) was accepted. The novelty of this research is that students are more active and interested in the learning process, students understand the material more easily, and students have a greater curiosity.